2020
DOI: 10.3329/bjb.v49i4.52537
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity and GC-MS analysis of n-butanol extract of quinoa (Chenopodium quinoa Willd.) leaves

Abstract: Dry leaves of quinoa (Chenopodium quinoa Willd.) were extracted in methanol and its n-butanol fraction was separated. Solvent was evaporated and antifungal bioassays were carried out against Macrophomina phaseolina using different concentrations (1.562, 3.125, 6.25, 12.50, 25, 50, 100, 200 mg/ml) of the extract in malt extract broth. The entire set of concentrations significantly controlled the fungal growth. The lowermost concentration of the extract (1.562 mg/ml) reduced M. phaseolina biomass by 62% over con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…lycopersici. Recently, Khan and Javaid (2020a) reported that n-hexane and chloroform fractions of methanolic stem extract of Chenopodium quinoa completely inhibited growth of Macrophomina phaseolina. Soil infected with Sclerotium rolfsii was amended with 3% concentration of dry plant biomass of C. album that significantly controlled the collar rot disease in chickpea (Ali et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…lycopersici. Recently, Khan and Javaid (2020a) reported that n-hexane and chloroform fractions of methanolic stem extract of Chenopodium quinoa completely inhibited growth of Macrophomina phaseolina. Soil infected with Sclerotium rolfsii was amended with 3% concentration of dry plant biomass of C. album that significantly controlled the collar rot disease in chickpea (Ali et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…β-sitosterol and γ-sitosterol (Khan & Javaid, 2020a, 2020b, 2020c, which could be responsible to inhibit the growth of M. phaseolina resulting in reduced disease incidence on mungbean plants. Literature also shows that soil amendment with other species of Chenopodium such as C. album reduced collar rot of chickpea caused by Sclerotium rolfsii (Ali et al, 2020) and basal rot of onion caused by Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Application of C. quinoa biomass as soil amendment significantly reduced disease incidence. Previous studies have shown that different parts of C. quinoa contain many antifungal compounds namely 9,12‐octadecadien‐1‐ol,(Z,Z)‐; 8,11‐octadecadienoic acid, methyl ester; hexadecanoic acid, 2‐hydroxy‐1‐(hydroxymethyl) ethyl ester; β‐sitosterol and γ‐sitosterol (Khan & Javaid, 2020a, 2020b, 2020c), which could be responsible to inhibit the growth of M. phaseolina resulting in reduced disease incidence on mungbean plants. Literature also shows that soil amendment with other species of Chenopodium such as C. album reduced collar rot of chickpea caused by Sclerotium rolfsii (Ali et al, 2020) and basal rot of onion caused by Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been cultivated in the Andean region for several thousand years (Jahanbkhsh et al, 2020). It contains phenolic compounds (Pereira et al, 2020), saponins, alakaloids, carotenoids, flavonol, terpenoids, peptides, phytosterols, and glycosides (Hernández‐Ledesma, 2019), with strong antifungal properties against M. phaseolina (Khan & Javaid, 2020). Previous studies regarding the use of biological control agents and dry biomass of plants to control charcoal rot of leguminous crops were generally focused on increase in yield of the crop while the effect of these amendments on histochemical aspects were ignored.…”
Section: Introductionmentioning
confidence: 99%